Evaluation of National Policy about Domestic Violence against Women in Iran - Aida Mehrad, Bahare Fallahi (Journal of Educational, Health and Community Psychology, 2014)
AbstractÂ One of the unpleasant behaviors that threats womenâ life and leads to various disquiets among family members is domestic violence. Prevention of Â this Â social dilemma and Â recognizing of Â its Â mechanism supposed as Â a Â vital Â and predictable fact in national policies. Into the bargain, it is enough necessary to determine the national policies for protecting women to meliorate mental health in society. The goal of current literature is looking at the factors that may contribute to domestic violence against women. Also, this paper evaluate position of women in constitute law, civil law and national policies in Iran with the purpose of womenâ protect in the society.Â Key word: Domestic violence, Women, National policy, Iran